EITI implementation: promoting transparency and accountability in extractive industry in Vietnam - Nguyen, Ngoc Quang (Tư pháp – Hà Nội, 2020)
Mining is a complicated industrial sector that requires high levels of transparency for good governance. The main challenges related to this sector includes corruption, tax fraud, ineffective revenue management and negative environmental and social world. Due to the complication of mining industry sector, among many global always aim to bring a better governance up - to - date, the Extractive Industry Transparency Initiative (EITI) is considered to be the most effective tool. The principles of EITI are to disclose relevant information during the mining chain, including: (i) Licensing, (ii) Production data, (iii) State - owned enterprises (SOE), (iv) Major revenues, (v) Local revenue, (vi) Revenue management; and (vii) Social World. By December 2018, there have been 52 countries implementing EITI already, including developed countries as the UK, US, Norway and developing countries as Indonesia, Myanmar, Philippines, Nigeria as well.